Seasonal dynamics of small-scale fisheries in the Adriatic Sea - GRATI, FABIO; ALADZUZ, ADMIR; AZZURRO, ERNESTO; BOLOGNINI, LUCA; CARBONARA, PIERLUIGI; ҪOBANI, MIMOZA; DOMENICHETTI, FILIPPO; DRAGICEVIC, BRANKO; DULCIC, JAKOV; ÐUROVIC, MIRKO; IKICA, ZDRAVKO; JOKSIMOVIC, ALEKSANDAR; et al. (Mediterranean Marine Science, 2018)
The main aim of the present study is to increase the knowledge on the seasonal dynamics of the set gears used by Adriatic small-scale fisheries (SSFs) through the collation of data (landings, fishing effort, composition of catches, length-frequency distributions of target species and economic value of landings) on target species,. The study focused on the three set gears mainly used in the basin: gillnets, trammel nets and traps. The results confirmed that SSFs are diverse, complex and dynamic, representing an economic and social engine and providing seafood and employment to local economies. In the Adriatic Sea, SSFs exploit coastal fishing grounds where the seasonal fluctuations of the physical and chemical parameters of the water column strongly influence the occurrence of the different species. Because of this, many different types of set gears are currently used to catch a pool of target species over the year. Fishermen use more than one set gear during the year and tend to increase the fishing effort when the target species concentrate inside the coastal areas during the recruitment or the spawning season. Accordingly, landings reached the highest values during such periods and often include a large portion of juveniles and/or spawners. The study highlighted that the lack of appropriate data and complete statistics is still one of the main constraints for most of the Adriatic coastal countries, as few countries have in place routinely monitoring programs while others are dealing mostly with estimates. These gaps often have the effect of marginalizing and undervaluing the real role of SSFs in a Blue Growth process.